Innovative models of care for the health facility of the future: a protocol for a mixed-methods study to elicit consumer and provider views. Issue 11 (16th November 2022) - Carrigan, Ann; Roberts, Natalie; Clay-Williams, Robyn; Hibbert, Peter D; Pomare, Chiara; Mahmoud, Zeyad; Maka, Katherine; Mitchell, Rebecca; Zurynski, Yvonne; Long, Janet C; Rapport, Frances; Arnolda, Gaston; et al.
Abstract : Introduction: To address the challenges of rapidly changing healthcare, governments and health services are increasingly emphasising healthcare delivery models that are flexible, person centred, cost-effective and integrate hospital services more closely with primary healthcare and social services. In addition, such models increasingly embed consumer codesign, integration of services, and leverage digital technologies such as telehealth and sophisticated medical records systems. Objectives: This paper provides a study protocol to describe a method to elicit consumer and healthcare provider needs and expectations for the development of innovative care models. Methods and analysis: A literature review identified six key models of care, supported by a common theme of consumer-focused care, along with the international evidence supporting the efficacy of these models. A mixed-methods study of the needs and expectations of consumer members and health providers who reside or work in the area of a new hospital catchment will be undertaken. They will complete a community-specific and provider-specific, short demographic questionnaire (delivered during the recruitment process) and be assigned to facilitator-coordinated online workshops comprising small focus groups. Follow-up interviews will be offered. Culturally and linguistically diverse members and Aboriginal and Torres Strait Islander Elders and their communities will also be consulted. Data will be analysed thematically (qualitative) and statistically (quantitative), and findings synthesised using a triangulated approach. Ethics and dissemination: The results will be actively disseminated through peer-reviewed journals, conference presentations and in a report to stakeholders. This study was reviewed and approved by the relevant Ethics Committee in New South Wales, Australia.